Enhanced piezoelectricity in Na and Ce co-doped CaBi4Ti4O15 ceramics for high-temperature applications - Zimeng Hu; Vladimir Koval; Hangfeng Zhang; Kan Chen; Yajun Yue; Dou Zhang; Haixue Yan (Journal of Advanced Ceramics, 2023)
The sodium (Na) and Ce co-doped calcium bismuth titanate (CBT; CaBi4Ti4O15) Aurivillius ceramics in a Ca1−x(Na0.5Ce0.5)xBi4Ti4O15 (CNCBT; doping content (x) = 0, 0.03, 0.05, 0.08 and 0.12) system were synthesized by the conventional solid-state sintering method. All compositions show a single-phase orthorhombic (space group: A21am) structure at room temperature. The shift of the Curie point (TC) towards lower temperatures (T) on doping results from the increased tolerance factor (t). The substitution-enhanced ferroelectric performance with large maximum polarization (Pm) and facilitated domain switching is evidenced by the developed electrical polarization–electric field (P–E) and electrical current–electric field (I–E) hysteresis loops. The piezoelectric coefficient (d33 = 20.5± 0.1 pC/N) of the x = 0.12 sample is about four times larger than that of pure CBT. The improved piezoelectric properties can be attributed to the high remanent polarization (Pr) and relatively high dielectric permittivity (ε′). In addition, multi-sized (micron and sub-micron) domain structures were observed in the CNCBT ceramics by the piezoresponse force microscope (PFM). The multiple-sized ferroelectric domain structure with smaller domains is beneficial to the easy domain switching, enhanced ferroelectric performance, and improved piezoelectric properties of the CNCBT ceramics. The designed Aurivillius-phase ferroelectric ceramics with the TC around 765 ℃ and high piezoelectric coefficient (d33) are suitable for high-temperature piezoelectric applications.